TIKTOK SHOP VS E-COMMERCE VS NEGARA: MENCARI TITIK KESEIMBANGAN DALAM BINGKAI EKONOMI KONSTITUSIONAL - Anuar, Yazrul; Hazmi, Raju Moh; Nazar, Jasman (Universitas Dharmawangsa, 2023)
This article aims to understand the concept of e-commerce and find a balance point in the constitutional economic framework regarding the prohibition on social media, TikTok shops merging into e-commerce. This research uses a juridical-nornative approach and is designed to be descriptive. The research results show: The concept of e-commerce is basically a